(untitled) (World Bulletin of Public Health, 2023)
Prokinetic drugs (prokinetics) are drugs that increase and coordinate muscle contractions of the gastrointestinal tract (GI tract), including coordination between different segments of the intestine, thereby enhancing the movement of intraluminal contents. Contemporary approaches to the use of prokinetics in the treatment of motor disorders of the gastrointestinal tract are considered in the overview. The results of studies of various classes of drugs with a prokinetic effect and aimed at various pathophysiological mechanisms, including a violation of antroduodenal coordination, manifested by subjective symptoms and objective delay in gastric emptying, are presented. The drug Domperidone, currently used in clinical practice and registered in Uzbekistan, still remains relevant. In the treatment of patients with functional dyspepsia, gastroparesis and gastroesophageal reflux disease, it is recommended to take it in combination with proton pump inhibitors. Domperidone has an antiemetic effect, possesses a positive safety profil when used according to registered indications